PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP KEMANDIRIAN KEUANGAN DAERAH PADA KABUPATEN/KOTA SE-JAWA TIMUR TAHUN 2014-2023 - Hidayat, Syakroni Arif; Anwar, Anwar; Suharsono, Agus; Laily, Yaen Miftakhul; Akbar, Muhamad Nanda Al Hakim; Maulana, Fajri (STKIP Pesisir Selatan, 2026)
This research aims to explain the effect of Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) and the General Allocation Fund (Dana Alokasi Umum/DAU) on Regional Financial Independence (Kemandirian Keuangan Daerah/KKD) of regency and municipal governments in East Java Province during the period 2014–2023. Regional financial independence is an important indicator for assessing the ability of local governments to finance governmental functions and development activities without excessive dependence on central government transfers. This study employs a quantitative approach with an associative research design. The population includes all regencies and municipalities in East Java, using a saturated sampling technique that results in 29 regencies and 9 municipalities as research samples. Secondary data in the form of realized PAD and DAU were obtained from the Directorate General of Fiscal Balance and Statistics Indonesia. Data analysis methods include descriptive statistics, multiple linear regression, classical assumption tests, and partial and simultaneous significance tests. The results indicate that PAD has a positive and significant effect on regional financial independence, while DAU has a negative and significant effect on regional financial independence. Simultaneously, PAD and DAU significantly affect regional financial independence.